(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
During this search, the polymer poly-aniline hydrochloride (PANI-HCL) was prepared with different weights before and after irradiation in the form of films using the casting method. The films were recorded with the cobalt element(CO60), which sends a gama (1.2) Mev for a period of (72) hours. The structural properties of the (FT-IR) were studied. The results showed that the active groups of the recorded polymer were consistent with the chemical composition and topographic study of the prepared film surfaces. The images showed that the recorded polymer is homogeneous and its color changes after irradiation. The electrical properties included the measurement of the hall effect and the continuous electrical conductivity and the behavior of the current and voltages where the results showed that the Hall coefficient of the polymer mixture recorded before and after the irradiation are carriers of the (n-type) and through the measurement of current- voltages show results that the polymer recorded conduct the behavior of ohmic before irradiation and walk Conduction of a semiconductor after irradiation. In addition, the results of electrical conductivity were shown to be less after irradiation.